ANTENOR ORREGO’S EDUCATIONAL THOUGHT - Robles Ortiz, Elmer (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
Peruvian thinker Antenor Orrego Espinoza’s work (1892-1960) is beyond dogmas and mental colonialism. With a new vision, he analyzes the historical process of Peru and Latin America in order to both address social problems and seek alternative solutions. Education is among these problems and alternatives, and is linked to its philosophical, sociological, political, and aesthetic ideas. He conceived education as a tool to train cultured people and citizens, end the tyranny of ignorance, and build awareness of our reality and the pressing need to transform it. From his thought, an education emerges completely centered on humankind: an education that reveals students’ potentials and guides and ennobles them into the human development process towards the fullness of the human being; an education imbued with creativity and which drives social change. He believes that, since nature and society are never static, education must be either consequently. Therefore, the school should prepare students’ brains to respond creatively to the evolving problems of their environment and the world. Thus, education will be like life itself: dynamic, ever-flowing, and a continuous revelation. And it must advocate for Latin America integration. He conceives an integrated, dynamic, and flexible university; open to all currents of thought, creator and disseminator of culture, full of authenticity—that must respond to the reality in which it is settled. This article tries to make reflection about Orrego’s educational thought and concerns: its definition and purpose, content and education agents, strategies of teaching-learning process, university education, and the educational and cultural integration of Latin America.